Wikipedia as an object of research - Tramullas, Jesús (Anuario ThinkEPI, 2015)
This short paper analyzes Wikipedia as an object of scientific research, contrasting various studies dealing with that popular encyclopedia. The conclusion is that Wikipedia, as a manifestation of collaborative production and consumption of knowledge, is a valid subject of scientific research.